2010
DOI: 10.1007/bf03391604
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Resources for Health in Developing Countries

Abstract: With increased globalization and interdependence among countries, sustained health worker migration and the complex threats of rapidly spreading infectious diseases, as well as changing lifestyles, a strong health workforce is essential. Building the human resources for health should not only include healthcare professionals like physicians and nurses, but must take into consideration community health workers, mid-level workers and strengthened primary healthcare systems to increase coverage and address the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 63 publications
5
91
0
1
Order By: Relevance
“…Similarly, the call is underpinned by the changing dynamics in the new public health arena (Baum, 2008) coupled with the recent global financial crisis, which has compelled most governments in high-income countries (HICs) and low-and middle-income countries (LMICs) as well as donor agencies to cut down on budgetary allocations for public health and health promotion interventions. The case becomes more challenging as most public health services are now being moved to the local level in both HICs and LMICs alike (Bangdiwala, Fonn, Okoye & Tollman, 2010;Green, 2013) thus placing a huge responsibility on local public health managers. To meet these global challenges, local public health managers need to think globally and act locally, and to also strategically equip and reorient themselves to the basic tenets of evidence-based public health (EBPH).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the call is underpinned by the changing dynamics in the new public health arena (Baum, 2008) coupled with the recent global financial crisis, which has compelled most governments in high-income countries (HICs) and low-and middle-income countries (LMICs) as well as donor agencies to cut down on budgetary allocations for public health and health promotion interventions. The case becomes more challenging as most public health services are now being moved to the local level in both HICs and LMICs alike (Bangdiwala, Fonn, Okoye & Tollman, 2010;Green, 2013) thus placing a huge responsibility on local public health managers. To meet these global challenges, local public health managers need to think globally and act locally, and to also strategically equip and reorient themselves to the basic tenets of evidence-based public health (EBPH).…”
Section: Introductionmentioning
confidence: 99%
“…There is a global crisis in the health workforce, expressed in acute shortages and maldistribution of health workers, geographically and professionally. This massive global shortage, though imprecise quantitatively, is estimated at more than 4 million workers (Bangdiwala et al, 2010). Africa bears one-third of the global burden of diseases but contain only 3% of the global health workforce.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of health care workers conducted in six African countries found that the leading factors behind health care worker migration included better work conditions, efforts to obtain additional education and training, and higher or more realistic remuneration (4,49). Other factors, including job satisfaction, perceptions of work environment, ability to utilize one's own professional skills, organizational environment, career opportunities, trust in management of health services, general political and administrative governance, bureaucratic efficiency and fairness, availability of protective gear (especially from HIV/AIDS), welfare, and benefits to health care workers during employment and retirement, have been listed as reasons for international migration (11,17,33,44).…”
Section: Issues Across the Globementioning
confidence: 99%
“…The current primary nursing care environment strengthens the call for better data as well as for effective operational research and evaluation. This research is required to inform policy makers and senior managers of the most current and effective solutions in primary care and to guide efforts to develop a sustainable health care workforce to address the health of an entire country's population (4).…”
Section: More Consistent Datamentioning
confidence: 99%